2012
DOI: 10.1167/iovs.12-9708
|View full text |Cite
|
Sign up to set email alerts
|

A Short-Term In Vivo Experimental Model for Fuchs Endothelial Corneal Dystrophy

Abstract: Restoration of transparency and corneal thickness demonstrated that the TE-FECD grafts were functional in vivo. This novel FECD seven-day living model suggests a potential role for tissue engineering leading to FECD cell rehabilitation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 37 publications
0
16
0
Order By: Relevance
“…This could explain previous results showing that an endothelium tissue-engineered using cultured corneal endothelial cells from patients with end-stage FECD cells retains some functionality. 24 Currently, the only treatment for FECD is transplantation of an allogeneic corneal endothelium, using donor tissue. This work opens the door to a new therapeutic concept, where rehabilitation of a diseased FECD endothelium could potentially be achieved through reimplantation of a new corneal endothelium tissue engineered from cultured autologous endothelial cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This could explain previous results showing that an endothelium tissue-engineered using cultured corneal endothelial cells from patients with end-stage FECD cells retains some functionality. 24 Currently, the only treatment for FECD is transplantation of an allogeneic corneal endothelium, using donor tissue. This work opens the door to a new therapeutic concept, where rehabilitation of a diseased FECD endothelium could potentially be achieved through reimplantation of a new corneal endothelium tissue engineered from cultured autologous endothelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…We also demonstrated that the diseased endothelial cells of clinically decompensated FECD corneas, when cultured and seeded on a devitalized stromal carrier and transplanted into the living animal eye, can recover active pump function and restore corneal transparency for at least 7 days after transplantation. 24 The partial recovery in culture of these end-stage FECD endothelial cells harvested from the central and most diseased part of the cornea has opened the door to a new perspective, which is herein analyzed from an ''oxidation standpoint.' ' The goal of this study was to investigate the effect of cell culture on the oxidative imbalance documented in FECD corneal endothelial cells.…”
mentioning
confidence: 99%
“…The barrier function depends on the ability of endothelial cells to fully cover the stromal surface and to maintain cell to cell tight junctions, and both appear to be intact until end stage disease. A study suggests that FECD endothelial cells are capable of migration and division to fully populate a stromal surface despite a reduced ability to control stromal water content (Haydari et al, 2012). In this study, endothelial cells from human FECD patients were grown on devitalized stroma in vitro.…”
Section: Hernandezmentioning
confidence: 98%
“…In this study, endothelial cells from human FECD patients were grown on devitalized stroma in vitro. It was demonstrated that the corneal stroma fully covered by FECD endothelial cells had a thickness of 770 mm compared to stroma covered by normal endothelium (520 mm), and both were thinner than stromal carrier only (1190 mm) (Haydari et al, 2012). Overall integrity of the cellecell tight junctions was found even at low human or bovine endothelial cell density in an in vitro endothelial cell culture model, suggesting that the endothelium may employ compensatory mechanisms to maintain barrier integrity at low density (Singh et al, 2013).…”
Section: Hernandezmentioning
confidence: 99%
“…18 Most studies, including our own unpublished data, show that FECD CEnCs can be passaged for only one to two passages, unless transduced with Simian virus 40 or E6/E7 oncogenes, because of low proliferative potential and rapid senescence. 19 To date, there is a scarcity of evidence regarding how to generate uniform and functional corneal endothelium from SCs, and corneal tissue remains the only source of normal or FECD HCEnCs.…”
mentioning
confidence: 99%